Control as an Alternative to Corruption. Will It be an Option of the Current Economy in Ecuador? - Rizzo-Guambaña, Gabriel Ernesto (2021)
One of the functions of the General Comptroller of the State, according to article 212 of the Constitution of the Republic of Ecuador, is the determination of administrative responsibilities; faulty civilians and even criminal liability, related to aspects of procedures subject to control. However, as of 2015, this attribution is subtracted through a simple Presidential Decree, limiting this control body to carry out management audits. According to the former president of Ecuador, it would be the best way to avoid corruption, since public institutions are obliged to render accounts on an annual basis. This work deals with the importance of performance auditing as a fundamental tool to control the efficiency and effectiveness that any public or private company must apply to measure the achievement of its objectives. Additionally, it constitutes a very important element for decision-making and reprogramming of the planning of its mission and short-term vision. For its development, we focus more on the Government field since there is more literature on the matter. The study was based on a documentary-based analytical research, we used inductive, analytical and synthesis as a research method. Reason for which, we came to the conclusion that the performance audit should not have been eliminated from the responsibilities that the General Comptroller of the State, CGE, Maintained in the period under review.